(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The present study sought in the Waldorf Pedagogy discourse the possibility of an education focused on the future of the human being, based on its proposition, which is to enable the subject to face the challenges of the contemporary world, integrating science and art, through of educational activities, artistic and craft practices, harmonizing the forces of thinking, feeling and doing. The objective of this research was to verify the relationship between the interest aroused by artistic and craft activities in relation to the formation of individual attitudes that express creativity, organization and collaboration, in a group of students enrolled in regular Elementary School in a small town in the interior paulista, and that after school, participate in an educational project, based on this pedagogical orientation. As a theoretical framework, we rely on Rudolf Steiner (2005,2015), Schiller (1990), Lanz (1990,2003,2005), Hahn (2007), and Walter Benjamin (2014).